2022
DOI: 10.1007/s00270-021-03051-5
|View full text |Cite
|
Sign up to set email alerts
|

“Real-World Study of a Dual-Layer Micromesh Stent in Elective Treatment of Symptomatic and Asymptomatic Carotid Artery Stenosis (ROADSAVER)”

Abstract: Purpose Endovascular carotid artery stenosis treatment is associated with a higher peri- and early post-procedural stroke risk relative to surgery. Dual-layer micromesh carotid stents were specifically designed for improved plaque coverage to reduce the cerebral embolization risk and related ischemic events. ROADSAVER study aims to further confirm the safety and efficacy of the Roadsaver™ dual-layer micromesh stent for the treatment of elective patients with carotid artery stenosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Recently, other real-world studies have also confirmed the excellent safety and performance of DLMS during CAS in non-selected patient populations 28,45,48,51,52 . Finally, the ROADSAVER study, the largest real-world DLMS study to date, with close to 2,000 elective patients enrolled, further complements the available clinical evidence on DLMS use in current CAS 53 .…”
Section: Dual-layer Micromesh Stentsmentioning
confidence: 85%
“…Recently, other real-world studies have also confirmed the excellent safety and performance of DLMS during CAS in non-selected patient populations 28,45,48,51,52 . Finally, the ROADSAVER study, the largest real-world DLMS study to date, with close to 2,000 elective patients enrolled, further complements the available clinical evidence on DLMS use in current CAS 53 .…”
Section: Dual-layer Micromesh Stentsmentioning
confidence: 85%
“…The ROADSAVER is a prospective, multi-center observational study that enrolled approximately 2000 patients across Europe, which evaluated the safety and efficacy of the Roadsaver stent at 30 days and 1 year. The study completion was July 2022, and we await the results for better analysis and evaluation of the Roadsaver carotid stent [25].…”
Section: Discussionmentioning
confidence: 99%
“…The DLS thrombosis rate in the present meta-analysis (0.8%) seems to be similar to the results reported by Moulakakis et al 36 They described a series of 674 CAS with standard stents, having four cases (0.6%) of acute thrombosis, possibly secondary to carotid dissections and overlapping of a second stent. 37 …”
Section: Discussionmentioning
confidence: 99%